A Diagnosis-Based Clustering and Multipath Routing Protocol for Wireless Sensor Networks. (2nd September 2012) - Liu, Wenjun; Zhang, Shukui; Fan, Jianxi
Abstract : In wireless sensor networks, it is of great importance for fault diagnosis to ensure the gathering information accuracy and reduce energy additionally consumed by faulty nodes, for the deployment of a large number of sensor nodes in hostile environment. In this paper, we propose an energy-efficient data collection protocol which consists of clustering and multipath routing. Clustering based on fault diagnosis eliminates the possibility of cluster heads (CHs) acting by faulty nodes which reduce energy consumption and fault information transmission. Multipath routing provided by directed acyclic graph (DAG) increases system fault tolerance. Furthermore, clustering and multihop routing consider residual energy and routing cost, respectively; thus balanced energy consumption is achieved. Performance analysis shows that the message complexity disseminated in clustering and fault diagnosis is acceptable. Simulations demonstrate that the protocol has better energy efficiency compared with other related protocols.